Phase change heat storage foam thermal insulation material and preparation method thereof
By adding phase-change microcapsules to the foam insulation material and combining them with regenerated micropowder and slag powder, the problems of low resource utilization and poor thermal inertia are solved, which significantly improves the insulation effect and environmentally friendly utilization of solid waste, and reduces energy Consumption and carbon emissions.
Patent Information
- Application Number
- CN202411241774.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-31
AI Technical Summary
The problem of low resource utilization rate of recycled micropowder and poor comprehensive thermal inertia after forming foam insulation materials.
Phase change microcapsules are combined with regenerated micropowder and slag powder to prepare phase change heat storage foam insulation materials through specific ratios and preparation methods, improve the insulation effect of foam insulation materials, and realize efficient resource utilization of solid waste.
It significantly improves the insulation effect of foam insulation materials, improves indoor environment comfort, reduces heat loss in buildings, reduces dependence on traditional energy, and reduces carbon emissions, achieving efficient resource utilization of solid waste .
Smart Images

Figure CN119219372A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization and relates to a phase-change heat storage foam insulation material and a preparation method thereof. Background Art
[0002] As a building energy-saving material containing a large number of pores, foam insulation materials have the characteristics of high porosity, low density, good sound insulation and fire resistance, and good thermal insulation. Traditional foam insulation materials are mostly prepared with ordinary Portland cement, but the production process of cement has disadvantages such as serious pollution and huge energy consumption. In order to effectively reduce energy consumption and environmental load, geopolymer materials have become one of the substitutes for Portland cement, and foam insulation materials prepared with fly ash, slag and other main raw materials have received widespread attention and attention. In recent years, with the rapid development of infrastructure construction and the increasing shortage of traditional volcanic ash materials such as fly ash and slag, how to effectively develop or comprehensively utilize various low-activity solid waste materials has become one of the core and hot topics in the current research field.
[0003] Recycled powder (RP) refers to the fine powder produced in the process of recycling coarse and fine aggregates from waste concrete, which accounts for about 20% of the mass of waste concrete. RP contains a large amount of silicon-calcium components and is a solid waste with potential application value. The recycled powder has a small particle size and strong hydrophilicity. It can form a foam insulation material matrix with suitable viscosity with water, but due to its low activity, the strength of the prepared matrix material is difficult to meet actual requirements. Slag, as a by-product of blast furnace steelmaking, can be quickly activated and generate strength under the action of an alkaline activator. Therefore, the recycled powder and slag form a binary solid waste system, which can not only form a matrix with suitable viscosity and strength, but also make efficient and comprehensive utilization of solid waste.
[0004] However, the comprehensive thermal inertia of foam insulation materials prepared from alkali-activated recycled micropowder-slag is poor. Studies have found that adding phase change materials (PCM) to wall panels or floors can significantly increase the thermal capacity of buildings and effectively reduce indoor and outdoor temperature fluctuations. For example, adding PCM to gypsum to obtain phase change gypsum board can not only significantly reduce the temperature fluctuation inside the building, but also save 30% of energy. For example, adding PCM to concrete can reduce the thermal conductivity of concrete and improve the thermal inertia of concrete. However, the addition of PCM will lead to a decrease in the mechanical properties of concrete, so appropriate dosage and addition method are required in the application to balance thermal and mechanical properties. Summary of the invention
[0005] The present invention aims to solve the technical problems of low resource utilization rate of recycled micropowder and poor comprehensive thermal inertia of foam insulation materials after molding, and provides a phase change heat storage foam insulation material. The addition of phase change microcapsules can improve the insulation effect of the foam insulation material, thereby improving the resource utilization rate of solid waste.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides a phase-change heat storage foam insulation material, which is prepared from the following components in percentage by mass: 35-40% of recycled micropowder, 15-18% of slag powder, 0.5-4% of phase-change microcapsules, 2-3% of alkali activator, 1.2-2% of prefabricated foam, 40-45% of water, 0.2-0.4% of water reducer, and 0.6-0.9% of coagulant. The slurry water-to-solid ratio of the phase-change heat storage foam insulation material is 0.8.
[0008] The particle size of the regenerated micropowder in the technical solution of the present invention is less than 100 μm, and the median particle size D50 is 17.4 μm.
[0009] The particle size of the slag powder in the technical solution of the present invention is less than 100 μm, and the average particle size D 50 It is 18.6μm.
[0010] The core material of the phase-change microcapsule in the technical solution of the present invention is n-octadecane, the wall material is polymethyl methacrylate, and the content of the core material is 80%.
[0011] The alkaline activator in the technical solution of the present invention is sodium hydroxide particles.
[0012] The prefabricated foam described in the technical solution of the present invention is prepared by foaming saponin plant protein.
[0013] The water reducing agent in the technical solution of the present invention is a polycarboxylic acid water reducing agent, the water reducing rate is 25% to 35%, and the pH value is 6.0 to 7.5.
[0014] The coagulant described in the technical solution of the present invention is calcium chloride hexahydrate particles.
[0015] The present invention also provides a method for preparing the above-mentioned phase change heat storage foam insulation material, comprising the following steps:
[0016] 1) Mixing the recycled micro powder, slag powder and phase change microcapsules uniformly to obtain a precursor material;
[0017] 2) Dissolve the alkaline activator in water to obtain an aqueous solution, and let it stand for 1 hour to eliminate the effect of temperature on the hydration reaction of the material;
[0018] 3) uniformly mixing the water reducing agent and the coagulant with the precursor material obtained in step 1);
[0019] 4) putting the material obtained in step 3) into a stirring device, adding the aqueous solution obtained in step 2), and stirring rapidly for 2 minutes and then stopping;
[0020] 5) Add the prefabricated foam into a mixer and stir at a low speed for 20 seconds to obtain a phase change heat storage foam insulation material slurry;
[0021] 6) The slurry obtained in step 5) is placed in a mold, covered with a plastic film, and demoulded after curing for 1 day, and then cured to an age of 28 days.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] Compared with traditional cement-based foam insulation materials, the phase change heat storage foam insulation material of the present invention, on the one hand, the addition of phase change microcapsules can improve the thermal insulation effect of the foam insulation material, improve the comfort of the indoor environment, reduce the heat loss of the building and reduce the dependence on traditional energy, which has a positive impact on building energy conservation and environmental protection; on the other hand, the carbon emissions generated during the production process of the phase change heat storage foam insulation material are lower, and the resource utilization of solid waste can be realized, reducing the negative impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the particle size distribution diagram of recycled micropowder, slag powder and phase change microcapsule.
[0025] Figure 2 This is the appearance and cross-sectional view of the phase change heat storage foam insulation material prepared in Example 1.
[0026] Figure 3 The dry density test results of the thermal insulation materials prepared in Comparative Example 2 and Examples 1 to 4 are shown.
[0027] Figure 4 These are the compressive strength test results of the thermal insulation materials prepared in Comparative Example 2 and Examples 1 to 4.
[0028] Figure 5 The water absorption test results of the thermal insulation materials prepared in Comparative Example 2 and Examples 1 to 4 are shown.
[0029] Figure 6 The thermal conductivity test results of the thermal insulation materials prepared in Comparative Example 2 and Examples 1 to 4 are shown.
[0030] Figure 7 The heat storage and release results of the thermal insulation materials prepared in Comparative Example 1, Comparative Example 2 and Example 3. DETAILED DESCRIPTION
[0031] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The test methods in the following examples are conventional methods unless otherwise specified.
[0032] In the following examples, the alkaline activator is sodium hydroxide granules, analytical grade, from Hengxing Reagent. The coagulant is CaCl2·6H2O, analytical grade, from Hengxing Reagent. The water reducer is polycarboxylic acid water reducer, from Shanghai Qichen Company, with a water reduction rate of 25% to 35% and a pH value of 6.0 to 7.5. The saponin plant protein foaming agent has the appearance of a transparent viscous liquid. After compression and foaming, the foam is white, the dilution multiple is 30 times, the water secretion rate is 34% in 30 minutes, and the defoaming time is 52 minutes. The phase change microcapsule is a commercially available 28°C phase change microcapsule (MPCM), the core material is n-octadecane, the wall material is polymethyl methacrylate (PMMA), the core material content is 80%, the melting point is 28°C, the enthalpy value is 160J / kg, the specific heat capacity is 1.5J / g, the thermal conductivity is 0.25W / (m·K), and the density is 0.85kg / m 3 , the particle size distribution is Figure 1 As shown, the median particle size D50 is 25 μm.
[0033] Recycled micro powder comes from waste concrete produced at a construction site. The waste cement slurry after the coarse aggregate is peeled off is crushed, the aggregate is removed, dried and ball milled (speed is 200-350r / min) for 1 hour and then passed through a 0.075mm sieve. The particle size analysis test results of RP show that the particle size distribution is between 0 and 100μm, and the median particle size D50 is 17.4μm. Figure 1 shown.
[0034] The slag powder is ground granulated blast furnace slag (GGBS), which comes from a steel mill in Kaifeng City. It is a by-product of blast furnace smelting pig iron. It is a glassy substance that cannot be crystallized after quenching in water in the molten state. It is obtained after grinding and drying. The minerals contained are mainly amorphous glass phase, and its main components are: CaO38.36%, SiO229.03%, Al2O3 15.17%, Fe2O3 2.9%, and the rest are impurities. The particle size distribution range of GGBS is between 1-100μm, and the median particle size D 50 is 18.6μm, such as Figure 1 shown.
[0035] Example 1
[0036] The components used in the preparation of the phase change heat storage foam insulation material in this embodiment are as follows: 490g of recycled micropowder, 210g of slag powder, 7g of phase change microcapsules, 35g of alkali activator sodium hydroxide particles, 20g of prefabricated foam, 560g of water, 3.5g of polycarboxylic acid water reducer, and 10.5g of accelerator calcium chloride hexahydrate.
[0037] Weigh each component according to the above ratio, and prepare the phase change heat storage foam insulation material according to the following steps:
[0038] 1) Mixing the recycled micro powder, slag powder and phase change microcapsules uniformly to obtain a precursor material;
[0039] 2) dissolving the alkaline activator solid sodium hydroxide particles in water to obtain an aqueous solution, and standing for 1 hour to eliminate the effect of temperature on the hydration reaction of the material;
[0040] 3) uniformly mixing the polycarboxylate water reducer and the coagulant calcium chloride hexahydrate with the precursor material obtained in step 1);
[0041] 4) putting the material obtained in step 3) into a stirring device, adding the aqueous solution obtained in step 2), and stirring rapidly for 2 minutes and then stopping;
[0042] 5) adding the prefabricated foam prepared by the physical foaming method into a mixer, stirring at a low speed for 20 seconds to obtain a phase change heat storage foam insulation material slurry, wherein the water-to-solid ratio of the slurry is 0.8;
[0043] 6) The slurry obtained in step 5) is placed in a mold, covered with a plastic film, placed in a curing box for standard curing for 1 day, and then demolded, and then cured to an age of 28 days to obtain a phase change heat storage foam insulation material.
[0044] Figure 2 The appearance and cross-sectional view of the phase change heat storage foam insulation material prepared in Example 1. It can be seen that the sample contains a large number of pores with uniform pore size distribution, and the closed small pores can effectively improve the thermal inertia of the foam insulation material.
[0045] Example 2
[0046] The components used in the preparation of the phase change thermal storage foam insulation material in this embodiment are as follows: 490g of recycled micropowder, 210g of slag powder, 21g of phase change microcapsules, 35g of sodium hydroxide particles as an alkali activator, 20g of prefabricated foam, 560g of water, 3.5g of polycarboxylic acid water reducer, and 10.5g of calcium chloride hexahydrate as a coagulant. The preparation steps are as follows:
[0047] Example 3
[0048] The components used in the preparation of the phase change thermal storage foam insulation material in this embodiment are as follows: 490g of recycled micropowder, 210g of slag powder, 35g of phase change microcapsules, 35g of alkali activator sodium hydroxide particles, 20g of prefabricated foam, 560g of water, 3.5g of polycarboxylic acid water reducer, and 10.5g of calcium chloride hexahydrate accelerator. The preparation steps are as follows: Example 1.
[0049] Example 4
[0050] The components used in the preparation of the phase change thermal storage foam insulation material in this embodiment are as follows: 490g of recycled micropowder, 210g of slag powder, 49g of phase change microcapsules, 35g of sodium hydroxide particles as an alkali activator, 20g of prefabricated foam, 560g of water, 3.5g of polycarboxylic acid water reducer, and 10.5g of calcium chloride hexahydrate as a coagulant. The preparation steps are as follows:
[0051] Comparative Example 1
[0052] The mass of the components used in preparing the common thermal insulation material in this embodiment is as follows: 490g of regenerated micro powder, 210g of slag powder, 35g of alkali activator sodium hydroxide particles, 560g of water, 3.5g of polycarboxylic acid water reducer, and 10.5g of calcium chloride hexahydrate accelerator. The preparation steps refer to Example 1.
[0053] Comparative Example 2
[0054] The components used in preparing the foam insulation material in this embodiment are as follows: 490g of recycled micropowder, 210g of slag powder, 35g of alkali activator sodium hydroxide particles, 20g of prefabricated foam, 560g of water, 3.5g of polycarboxylic acid water reducer, and 10.5g of calcium chloride hexahydrate accelerator. The preparation steps are as shown in Example 1.
[0055] The materials prepared in Comparative Example 1, Comparative Example 2, and Examples 1 to 4 were used as test pieces for performance testing: the test contents included dry density, compressive strength, thermal conductivity, water absorption, heat storage and release performance, and heat storage density.
[0056] (1) The dry density, compressive strength and water absorption rate tests were conducted in accordance with the reference standard "Foamed Concrete" (JG / T 266-2011). The dry density, compressive strength and water absorption rate of the thermal insulation materials prepared in Comparative Example 2 and Examples 1 to 4 are shown in Table 1. Figure 3-5 It can be seen that with the increase of the MPCM content, the dry density, compressive strength and water absorption of the phase change thermal storage foam insulation material samples prepared in Examples 1 to 4 all show a downward trend, and are lower than the dry density, compressive strength and water absorption of the foam insulation material of Comparative Example 2 (the horizontal axis is 0%).
[0057] (2) The thermal conductivity test refers to the standard "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials-Heat Flow Meter Method" (GB / T10295-2008). The specific test steps are as follows: The specimen is prepared with a size of 300mm×300mm×30mm, and the surface is kept basically flat. It is placed in a JW-III heat flow meter type thermal conductivity instrument, and the hot plate and cold plate temperatures are set to 35°C and 15°C. The preheating time is 30min, and the measurement time is 180min. The thermal conductivity test results of the thermal insulation materials prepared in Comparative Example 2 and Examples 1 to 4 are shown in Figure 6. It can be seen that with the increase in the amount of MPCM, the thermal conductivity of the phase change heat storage foam insulation material samples prepared in Examples 1 to 4 also shows a downward trend, and is lower than the thermal conductivity of the foam insulation material of Comparative Example 2 (the horizontal axis is 0%).
[0058] (3) The heat storage and release performance test method is as follows: prepare 5 EPS plastic insulation boards, 1 ordinary insulation material of comparative example 1, 1 foam insulation material specimen of comparative example 2, and 1 phase change heat storage foam insulation material specimen of embodiment 2, all with a size of 300mm×300mm×30mm. Overlap the EPS insulation board with the three test pieces respectively and glue them firmly with sealant to build 3 thermal insulation enclosure structures. Place a temperature sensor at the center of the inner wall of the test piece, and place a temperature sensor at the center of the enclosure structure. By detecting the data on the temperature recorder and drawing the temperature-time change curve, the temperature regulation and heat storage and release capacity of the phase change insulation board can be characterized.
[0059] The heat storage and release results of the thermal insulation materials prepared in Comparative Example 1, Comparative Example 2 and Example 3 are as follows: Figure 7 As shown, the heat storage and release curves of the inner wall center of the three specimens are recorded as a, c, and e, and the heat storage and release curves of the inner center of the three enclosure structures are recorded as b, d, and f. Figure 7 -a is the heat storage result, Figure 7 -b is the result of exothermic reaction. Figure 7 -a It can be seen that compared with ordinary insulation materials (line a), the decrease in the temperature rise rate of foam insulation materials (line c) is due to the presence of more air pores inside it, which makes its thermal conductivity lower and thus has a certain thermal inertia; compared with foam insulation materials, the temperature rise rate of phase change heat storage foam phase change plate (line e) shows a further decrease, which is due to the presence of not only more air pores but also a certain amount of phase change microcapsules inside it. When the two are coupled, the air pores provide a lower overall thermal inertia for the matrix, and as the temperature continues to rise to the phase change point of the phase change microcapsules, the internal phase change material melts from solid to liquid and absorbs heat, which further delays the temperature rise time inside the test device and improves the overall thermal inertia and heat storage capacity of the material.
[0060] from Figure 7-b It can be seen that compared with ordinary thermal insulation materials (line a), the phase change thermal storage foam phase change board (line e) has a slower temperature drop trend when exposed to the external low temperature environment, which shows that it has higher thermal inertia. The air pores formed by introducing prefabricated foam inside the phase change thermal storage foam board can effectively reduce the thermal conductivity of the material, thereby delaying the temperature drop inside it; and the phase change thermal storage foam phase change board not only enhances its own thermal inertia by introducing prefabricated foam, but also when the temperature drops to the phase change point of its internal phase change microcapsules, its internal phase change material will solidify from liquid phase to solid phase and release heat, which further delays the temperature drop inside the device.
[0061] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.
Claims
1. A phase change heat storage foam insulation material, characterized in that: The phase change heat storage foam insulation material is prepared from the following components in percentage by mass: 35-40% recycled micropowder, 15-18% slag powder, 0.5-4% phase change microcapsules, 2-3% alkali activator, 1.2-2% prefabricated foam, 40-45% water, 0.2-0.4% water reducer, and 0.6-0.9% coagulant. The water-to-solid ratio of the slurry of the phase change heat storage foam insulation material is 0.
8.
2. The phase change heat storage foam insulation material according to claim 1, characterized in that: The particle size of the regenerated micro powder is less than 100 μm, and the median particle size D50 is 17.4 μm.
3. The phase change heat storage foam insulation material according to claim 1, characterized in that: The particle size of the slag powder is less than 100 μm, and the median particle size D 50 It is 18.6μm.
4. The phase change heat storage foam insulation material according to claim 1, characterized in that: The core material of the phase change microcapsule is n-octadecane, the wall material is polymethyl methacrylate, and the content of the core material is 80%.
5. The phase change heat storage foam insulation material according to claim 1, characterized in that: The alkaline activator is sodium hydroxide particles.
6. The phase change heat storage foam insulation material according to claim 1, characterized in that: The prefabricated foam is prepared by foaming saponin plant protein.
7. The phase change heat storage foam insulation material according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer with a water reduction rate of 25% to 35% and a pH value of 6.0 to 7.
5.
8. The phase change heat storage foam insulation material according to claim 1, characterized in that: The coagulant is calcium chloride hexahydrate particles.
9. The method for preparing the phase-change heat storage foam insulation material according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) Evenly mix the recycled micro powder, slag powder and phase change microcapsules to obtain a precursor material; 2) Dissolve the alkaline activator in water to obtain an aqueous solution, and let it stand for 1 hour to eliminate the effect of temperature on the hydration reaction of the material; 3) uniformly mixing the water reducing agent and the coagulant with the precursor material obtained in step 1); 4) Place the material obtained in step 3) into a stirring device, add the aqueous solution obtained in step 2), and stir rapidly for 2 minutes before stopping; 5) Add the prefabricated foam into the mixer and stir at a low speed for 20 seconds to obtain a phase change heat storage foam insulation material slurry; 6) The slurry obtained in step 5) is placed into a mold, covered with a plastic film, and demoulded after curing for 1 day, and then cured to an age of 28 days.
